Understanding of Technical Terms and Contents of Informed Consent Forms for Sedative Gastrointestinal Endoscopy Procedures - Ihnsook Jeong, RN, PhD; Sunmi Park, RN, MSN; Jae Sim Jeong, RN, PhD (Elsevier, 2013)
Purpose: This was a cross-sectional study designed to evaluate the subjective understanding of technical terms and contents of the informed consent forms given to patients about to undergo conscious sedative upper gastrointestinal endoscopy. Methods: A group of conveniently selected 180 patients, who were undergoing sedative endoscopy were recruited in the endoscopy procedure room in a tertiary hospital from June to July 2011. Data were collected with a structured questionnaire. Results: The average number of terms exposed was 8.12 out of 10 items, the average number of terms understood well by the patients was 5.53 out of 10 items, and the average number of right answers was 3.30 out of 5 items, and the percent of correct answers ranged from 26.1% to 90.0%. The exposure to terms differed by gender, education, and previous exposure to sedative endoscopy procedures. The number of "understanding of the terms well" responses differed according to age and previous exposure to sedative endoscopy procedures, and the correct answer rate was differed by education. Conclusion: The understanding of the terms and knowledge about the procedures were disappointing. Therefore, sufficient explanations should be provided to the patients. While the informed consent was taken by doctors, the level of understanding should be monitored by nurses. In particular, subjects who did not have any previous experience with endoscopy procedures showed relatively lower level of understanding. We recommend that medical terms should be replaced with more common and nontechnical words in consent forms.